Scholarship holders abroad: returnees in the academic community in Serbia - Vasojević, Nena, A.; Krnjaić, Zora T.; Kirin, Snežana D. (Sociološki pregled, 2018)
This paper deals with our highly educated professionals who studied abroad as scholarship holders at post-academic studies and then returned and found employment in Serbia. The aim of this paper is to examine how this group of returnees employed at faculties and scientifc institutes in Serbia assess their experience of studying abroad. The assessments of the returnees were gathered through a quesstionaire. Tese assessments were on the extent to which the returnees felt their education abroad inﬂuenced their employment in Serbia, the opportunies to apply the acquired knowledge and to participate in decision-making at the workplace, and, fnally, on how diﬀerent they felt from their colleagues who acquired all their education and work experience in their own country. To better understand the situation of returnees, a special questionnaire also gathered theKeywords: highly educated professionals, scholarship holders, migration, returnees, academic communityassessments of their colleagues on these issues.